Historical thinking in higher education : an ALTC discipline-based initiative. - Hughes-Warrington, Marnie; Roe, Jill; Nye, Adele; Bailey, Matthew; Peel, Mark; Russell, Penny; Laugeson, Amanda; Deacon, Desley; Kiem, Paul; Trent, Faith (Australian Learning and Teaching Council, 2009)
Much research has been undertaken on the development of historical thinking in early childhood, primary and secondary education. This research provides the first tertiary-level study of staff and student perceptions of the nature, development and purposes of historical thinking, in order to identify opportunities for sector-wide projects in curriculum and assessment-task design and the articulation of standards of achievement. In 2008-9, 1445 first and third year undergraduate students and 50 academic staff in 11 Australian universities in five states and one territory completed questionnaires and interviews focused on historical thinking. Analysis of the data revealed a surprisingly consistent pattern of responses among students and staff and highlighted multiple opportunities for sector-wide development. Recommendations are included. [p.7, ed]